The Zero Power Rule states that any non-zero number raised to the power of zero is equal to 1.
Therefore, 63^0 = 1
Apply the Zero Power Rule of Integer Exponents to solve 63^0
16 answers
Apply the Zero Power Rule of Integer Exponents to solve 2.3+(−1.478)^0
The Zero Power Rule states that any non-zero number raised to the power of zero is equal to 1.
Therefore, (-1.478)^0 = 1.
Thus, 2.3 + (-1.478)^0 = 2.3 + 1 = 3.3.
Therefore, (-1.478)^0 = 1.
Thus, 2.3 + (-1.478)^0 = 2.3 + 1 = 3.3.
Apply the Zero Power Rule of Integer Exponents to solve −4^0⋅15
The Zero Power Rule states that any non-zero number raised to the power of zero is equal to 1.
Therefore, (-4)^0 = 1.
Thus, (-4)^0 * 15 = 1 * 15 = 15.
Therefore, (-4)^0 = 1.
Thus, (-4)^0 * 15 = 1 * 15 = 15.
Apply the Zero Power Rule of Integer Exponents to solve −4^0x15
The given expression is (-4^0) * 15.
According to the Zero Power Rule, any non-zero number raised to the power of zero is equal to 1.
Therefore, (-4)^0 = 1.
Thus, the expression simplifies to 1 * 15 = 15.
According to the Zero Power Rule, any non-zero number raised to the power of zero is equal to 1.
Therefore, (-4)^0 = 1.
Thus, the expression simplifies to 1 * 15 = 15.
its not working 15 or 1
Apologies for the confusion.
The Zero Power Rule states that any non-zero number raised to the power of zero is equal to 1. However, when it comes to negative numbers, it is important to distinguish the position of the negative sign.
For the expression -4^0 * 15, we need to evaluate the exponent first. Since anything raised to the power of zero is equal to 1, we have:
-4^0 * 15 = -1 * 15 = -15
Thus, the value of the expression is -15.
The Zero Power Rule states that any non-zero number raised to the power of zero is equal to 1. However, when it comes to negative numbers, it is important to distinguish the position of the negative sign.
For the expression -4^0 * 15, we need to evaluate the exponent first. Since anything raised to the power of zero is equal to 1, we have:
-4^0 * 15 = -1 * 15 = -15
Thus, the value of the expression is -15.
Apply the Zero Power Rule to create an equivalent expression to 4/3(−2+1^0).
To apply the Zero Power Rule, we evaluate any exponent of zero as equal to 1.
In the given expression, 1^0 = 1.
Therefore, an equivalent expression to 4/3(-2+1^0) would be:
4/3(-2+1) = 4/3(-1)
In the given expression, 1^0 = 1.
Therefore, an equivalent expression to 4/3(-2+1^0) would be:
4/3(-2+1) = 4/3(-1)
Solve the expression 2(1.6^0+7)−4.9^0
Using the Zero Power Rule, we evaluate any exponent of zero as equal to 1.
So, 1.6^0 = 1 and 4.9^0 = 1.
Now we can simplify the expression:
2(1.6^0 + 7) - 4.9^0 = 2(1 + 7) - 1 = 2(8) - 1 = 16 - 1 = 15.
Thus, the value of the expression is 15.
So, 1.6^0 = 1 and 4.9^0 = 1.
Now we can simplify the expression:
2(1.6^0 + 7) - 4.9^0 = 2(1 + 7) - 1 = 2(8) - 1 = 16 - 1 = 15.
Thus, the value of the expression is 15.
Apply the Zero Power Rule of Integer Exponents to solve 2.3+(−1.478)0.
apply the zero power rule to create an equivalent expression 4/3(-2+1'0).
@Bot GPT 3.5
Apply the zero power rule of integer exponents to solve -4^0 times 15
Apply the zero power rule of integer exponents to solve -4^0 times 15